INTEGRITAS DAN AKUNTABILITAS DALAM PEMERINTAHAN DESA (Studi Kasus: Penjualan Aset Tanah Kas Desa Pada Pemerintahan Desa Sumberasri, Kecamatan Nglegok Kabupaten Blitar - Jawa Timur) - Susilo, Ponco Tri (CITIZEN CHARTER, 2017)
ABSTRACT Integrity and accountability are indispensable to village governance, especially in the management of village asset wealth derived from the village treasury. The role of community participation is also needed to maintain, develop, assess the integrity and accountability of village governance. The subject matter of this research is the sale of village land which is designated for public facilities, village cash land, refugee land, village market. This research was conducted by qualitative descriptive method with data collection technique in depth interview to some informant and used secondary data as supporting depth level of information. This study measures how the integrity practices and accountability of Sumberasri Village government in the case of selling the land of village cash assets sold to private parties or individuals. The concept to dissect the results of research that is the concept of Integrity and the concept of accountability. Integrity is used four indicators, three of which have been implemented well, including loyalty indicators, indicators of harmony, and reliable indicators, while the indicators of cooperation have not been implemented effectively. Accountability uses three indicators including managerial accountability, financial accountability, public accountability. Only managerial accountability indicators are proven accountable, while other indicators have not been fully accountable. KeyWords : Integrity, Accountability, Assets